1978
DOI: 10.1029/jb083ib12p05989
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of isostasy in the world's oceans 1. Hawaiian‐Emperor Seamount Chain

Abstract: Cross‐spectral techniques have been used to analyze the relationship between gravity and bathymetry on 14 profiles of the Hawaiian‐Emperor seamount chain. The resulting filter or transfer function has been used to evaluate the state of isostasy along the chain. The transfer function can be best explained by a simple model in which the oceanic lithosphere is treated as a thin elastic plate overlying a weak fluid. The best‐fitting estimate of the elastic thickness of the plate is in the range 20–30 km. Analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
437
2
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 535 publications
(470 citation statements)
references
References 40 publications
29
437
2
2
Order By: Relevance
“…More important, a compilation of estimates of admittance from a variety of regions ( Figure 9) shows observed values of admittance to be consistently positive [e.g., Bayasgalan et al, 2005;D'Agostino and McKenzie, 1999;Komut et al, 2012;Fielding and McKenzie, 2012;McKenzie and Bowin, 1976;McKenzie and Fairhead, 1997;Tiley et al, 2003;Watts, 1978]. We are not aware of a single study reporting negative values for the Earth.…”
Section: Discussionmentioning
confidence: 91%
“…More important, a compilation of estimates of admittance from a variety of regions ( Figure 9) shows observed values of admittance to be consistently positive [e.g., Bayasgalan et al, 2005;D'Agostino and McKenzie, 1999;Komut et al, 2012;Fielding and McKenzie, 2012;McKenzie and Bowin, 1976;McKenzie and Fairhead, 1997;Tiley et al, 2003;Watts, 1978]. We are not aware of a single study reporting negative values for the Earth.…”
Section: Discussionmentioning
confidence: 91%
“…By comparing observed gravity anomalies with calculated anomalies based on simple elastic or viscoelastic models it has been possible to estimate the effective elastic thickness and how it may vary with crustal age. The main results of these studies, summarized in Watts (1978), is that surface loads formed at or near mid-ocean ridge crests are associated with relatively small values of the effective elastic thickness while surface loads formed on relatively old lithospheric plates are associated with relatively large values. Figure 2 is a plot of "isostatic response function" for the East Pacific rise crest and Hawaiian-Emperor seamount chain in the Pacific ocean.…”
Section: Discussionmentioning
confidence: 99%
“…The smaller value can be explained by taking into account the age of the Seamounts along the chain [Clague and Jarrard, 1973]. In a recent study, Watts [1978] observed the correlation between gravity and bathymetry data obtained from surface ships over several sections of the Pacific Ocean: the East Pacific Rise, the Hawaiian-Emperor Seamounts, and the Kuril Rise. He deduced that the relevant factor related to flexural rigidity is the age of the lithosphere at the time of loading.…”
Section: Short Wavelength Studymentioning
confidence: 99%
See 1 more Smart Citation
“…For this purpose, the relationship between geoid/ gravity and the topography in the spectral domain (admittance / coherence) is utilized for better understanding the isostatic response of the topographic loads, and for studies related to thermo-mechanical characterization of the oceanic lithosphere and/or sub-lithospheric upper mantle. Several researchers have effectively used this approach i) for evaluating isostatic response of the oceanic lithospheric using free-air gravity/ geoid and bathymetry admittance function (e.g., McKenzie and Bowin, 1976;Watts, 1978;Black and McAdoo, 1988); ii) for estimation of flexural rigidity of continental lithosphere through Bouguer gravity and topography coherence function (Forsyth, 1985;Lowry and Smith, 1994;McKenzie and Fairhead, 1997;Simons et al, 2000;Swain and Kirby, 2003). In the present study, we analyzed the admittance between bathymetry and residual geoid on two wavelength scales, one using degree-10 residual geoid for modeling upper mantle convection processes, and other using degree-50 residual geoid for understanding mode of isostatic compensation along the 85°E and Ninetyeast ridges.…”
Section: Admittance / Coherence Analysismentioning
confidence: 99%